ANALISIS HASIL BELAJAR SISWA TERHADAP PEMBELAJARAN MATEMATIKA DALAM KURIKULUM MERDEKA - Lagi, Supriadin; Yusuf, St. Muthmainnah; Fatmawati, Agustin (MEGA: Jurnal Pendidikan Matematika, 2024)
The objective of this study is to determine student learning outcomes relate to autonomous curriculum mathematics learning. This is a descriptive qualitative method with observation, interviews, tests, and documentation as data collection techniques. The data were analyzed using data reduction, data presentation, conclusion, and verification. Several important components were discovered, including lesson plan, learning implementation, evaluation of student’s outcomes, consequences of implementing an independent curriculum. The result showed that the assessment of student learning outcomes of first semesterreport cards and student scoresaverage of 100% which showed the completeness achievement criteria. Based on student test scores, almost all students achieved completeness in 88.9%.In the implications of Merdeka curriculum, especially in learning mathematics, students are more active, productive, and create a conducive class.Based on the observation sheet of learning activities from three activities and 19 statement items, it was discovered that they all appeared only during the learning process. As a result, the students were able to achieve high levels of achievement in mathematics while using Merdeka curriculum, indicating that the implementation was very effective.